Down‐regulation of c‐fos by shRNA sensitizes adriamycin‐resistant MCF‐7/ADR cells to chemotherapeutic agents via P‐glycoprotein inhibition and apoptosis augmentation12. Issue 8 (12th June 2013) - Shi, Ruizan; Peng, Hongwei; Yuan, Xiangfei; Zhang, Xiuli; Zhang, Yanjun; Fan, Dongmei; Liu, Xuyi; Xiong, Dongsheng
Abstract Multidrug resistance (MDR) is a major hurdle in the treatment of cancer. Research indicated that the main mechanisms of most cancers included so‐called "pump" (P‐glycoprotein, P‐gp) and "non‐pump" (apoptosis) resistance. Identification of novel signaling molecules associated with both P‐gp and apoptosis will facilitate the development of more effective strategies to overcome MDR in tumor cells. Since the proto‐oncogene c‐fos has been implicated in cell adaptation to environmental changes, we analyzed its role in mediating "pump" and "non‐pump" resistance in MCF‐7/ADR, an adriamycin (ADR)‐selected human breast cancer cell line with the MDR phenotype. Elevated expression of c‐fos in MCF‐7/ADR cells and induction of c‐fos by ADR in the parental drug‐sensitive MCF‐7 cells suggested a link between c‐fos and MDR phenotype. Down‐regulation of c‐fos expression via shRNA resulted in sensitization of MCF‐7/ADR cells to chemotherapeutic agents, including both P‐gp and non‐P‐gp substrates. Further results proved that c‐fos down‐regulation in MCF‐7/ADR cells resulted in decreased P‐gp expression and activity, enhanced apoptosis, and altered expression of apoptosis‐associated proteins (i.e., Bax, Bcl‐2, p53, and PUMA). All above facts indicate that c‐fos is involved in both P‐gp‐ and anti‐apoptosis‐mediated MDR of MCF‐7/ADR cells. Based on these results, we propose that c‐fos may represent a potential molecular target for resistant cancer therapy, and suppressing c‐fos gene expression may therefore be an effective means to temper breast cancer cell's MDR to cytotoxic chemotherapy. J. Cell. Biochem. 114: 1890–1900, 2013. © 2013 Wiley Periodicals, Inc.